Complex lower limb trauma, contusion and thrombosis of popliteal artery, vein graft - Liard, Washington; Mañana, Julio; Albo, Manuel (Cirugía del Uruguay, 1971)
We present a case of trauma tic lesion of the lower limb with thrombosis of the popliteal artery and vast necrosis of the skin. Sorne aspects of the treatment are considered: venous graft, surgical excision and skin grafting as a secondary procedure. By means of this treatment, anatomic and functional recovery of the limb was obteined.